SPECIFICITY OF FORMATION AND FUNCTIONING OF LEGAL ABBREVIATION TERMS IN MODERN ENGLISH LANGUAGE - Isroilova, Shokhida Dehkonovna (Educational Research in Universal Sciences, 2023)
Abbreviation terms are noted in five of the eight identified thematic groups of terms that unite units of different part-speech affiliation. These groups of terms, as a rule, denote objects and are less often noted in thematic groups of terms expressing abstract concepts. The number of abbreviations for various thematic groups depends on the number of terms representing these groups. This article discusses legal abbreviations in English.